2016
DOI: 10.1371/journal.pone.0147017
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Functional Responses Predict the Invasiveness and Ecological Impacts of Alien Herbivorous Snails

Abstract: Understanding determinants of the invasiveness and ecological impacts of alien species is amongst the most sought-after and urgent research questions in ecology. Several studies have shown the value of comparing the functional responses (FRs) of alien and native predators towards native prey, however, the technique is under-explored with herbivorous alien species and as a predictor of invasiveness as distinct from ecological impact. Here, in China, we conducted a mesocosm experiment to compare the FRs among th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 50 publications
1
43
0
Order By: Relevance
“…Alexander et al 2014a, b;Dick et al 2013Dick et al , 2017Paterson et al 2014;Laverty et al 2015;Xu et al 2016) have shown that the comparative FR methodology is rapid, efficient and effective at explaining and predicting the ecological damage caused by invasive species. However, in some cases the FR of invasive species is unremarkable when compared to those of native species, yet ecological damage is known to occur, as is the case with N. melanostomus and P. parva toward invaded communities (Barton et al 2005;Britton et al 2010;Gozlan et al 2010;Pagnucco and Ricciardi 2015).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Alexander et al 2014a, b;Dick et al 2013Dick et al , 2017Paterson et al 2014;Laverty et al 2015;Xu et al 2016) have shown that the comparative FR methodology is rapid, efficient and effective at explaining and predicting the ecological damage caused by invasive species. However, in some cases the FR of invasive species is unremarkable when compared to those of native species, yet ecological damage is known to occur, as is the case with N. melanostomus and P. parva toward invaded communities (Barton et al 2005;Britton et al 2010;Gozlan et al 2010;Pagnucco and Ricciardi 2015).…”
Section: Resultsmentioning
confidence: 99%
“…However, recent comparisons of invader and native functional responses (FRs) have often yielded excellent explanatory and predictive power of invader impact on native prey populations (Alexander et al 2014a, b;Dick et al 2013Dick et al , 2014Dick et al , 2017, and this has recently been extended to damaging herbivorous invaders (e.g. golden apple snail; Xu et al 2016). Indeed, the method is applicable to any taxonomic or trophic group due to the universal nature of organisms utilizing resources (Dick et al 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, while most invader/native functional response comparisons to date have examined predator-prey systems (e.g. Dick et al 2013), there are emerging studies involving herbivore-plant (Xu et al 2016) and plant-nutrient interactions (see RossiterRachor et al 2009). The latter study, by using completely different terminologies, led to the existence of essentially similar thinking by animal and plant invasion scientists-who, thus far, have had little collaborative interaction or consideration of each other's research.…”
mentioning
confidence: 99%
“…in ballast water tanks) and become established in new locations-where resources might be in short supply or already being utilised by existing native species. Similarly, invader establishment and spread may be facilitated by resource use patterns, again measurable by functional response studies, and species invasiveness as distinct from ecological impact (see Ricciardi and Cohen 2007) may also be correlated with functional responses (see Bovy et al 2015;Xu et al 2016). One aspect that might considerably improve the use of functional responses in such contexts would be incorporation of abundance, as per Parker et al (1999), which is essentially the numerical response that, together with the functional response, gives the total response (or total uptake rate; see Dick et al 2014).…”
mentioning
confidence: 99%